2015
DOI: 10.1080/10810730.2014.965371
|View full text |Cite
|
Sign up to set email alerts
|

Losing Weight on Reality TV: A Content Analysis of the Weight Loss Behaviors and Practices Portrayed onThe Biggest Loser

Abstract: A number of weight loss-related reality television programs chronicle the weight loss experience of obese individuals in a competitive context. Although highly popular, such shows may misrepresent the behavior change necessary to achieve substantial weight loss. A systematic, quantitative content analysis of Seasons 10-13 (n = 66 episodes) of The Biggest Loser was conducted to determine the amount of time and number of instances that diet, physical activity, or other weight management strategies were presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 36 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…The content and messaging about physical activity in television programs is, therefore, relevant to understanding how orientation to U.S. culture may relate to physical activity levels. Although there are high rates of obesity and sedentary behavior in the United States, actors and television personalities in U.S. media are disproportionately thin and toned (Robinson et al, 2008), and U.S. television programs that specifically depict weight loss may highlight physical activity as the main strategy for controlling body weight, while underrepresenting the role of diet (Klos et al, 2015). A recent content analysis of four programs targeting adolescent audiences found that physical activity was portrayed in half of the programs studied, and it was generally depicted as a positive activity motivated by enjoyment (O'Reilly-Duff et al, 2018).…”
Section: Physical Activity In Jamaican and Us Culturesmentioning
confidence: 99%
“…The content and messaging about physical activity in television programs is, therefore, relevant to understanding how orientation to U.S. culture may relate to physical activity levels. Although there are high rates of obesity and sedentary behavior in the United States, actors and television personalities in U.S. media are disproportionately thin and toned (Robinson et al, 2008), and U.S. television programs that specifically depict weight loss may highlight physical activity as the main strategy for controlling body weight, while underrepresenting the role of diet (Klos et al, 2015). A recent content analysis of four programs targeting adolescent audiences found that physical activity was portrayed in half of the programs studied, and it was generally depicted as a positive activity motivated by enjoyment (O'Reilly-Duff et al, 2018).…”
Section: Physical Activity In Jamaican and Us Culturesmentioning
confidence: 99%
“…Not only has health become something one does, but correct and visible performances become markers of mature, moral personhood and responsible citizenship (Gard and Wright 2005). In this context, the possession of a fat body is a visible mark of a stigmatised identity (Monaghan, Bombak, and Rich 2017;Aphramor 2005): overweight or obese people are always and already regarded as 'health offenders' (Tischner 2013,5) whose health problems are considered selfinflicted (Klos et al, 2015). Additionally, in the context of neoliberal rationalities and particularly austerity, this 'offence' is represented as having an impact on the health care of other citizens because of the 'burden' obesity places on already overstretched (under-funded) welfare services: the fat body then, becomes a concern of us all, encouraging a degree of social acceptability towards the everyday humiliation and prejudice towards larger people to 'encourage' them into good health practices (Major 'badness and sickness' that 'fat may as well be a four letter word' (Monaghan, 2007, 605).…”
Section: Why a Big Fat Frame?mentioning
confidence: 99%
“…Through a cascading network of issue interpretation the media are thought to play a key role in setting public understandings about a range of issues [41]. Others argue they co-construct the structures through which the public understand health and illness [42] and bolster the visibility and validity of contemporary health 'epidemics' [15,43]. Journalists admit that much of what drives reporting about health is newsworthiness and sensationalism, and that risk is a key way of garnering public attention [44].…”
Section: Introductionmentioning
confidence: 99%